2024
DOI: 10.1371/journal.pgph.0002810
|View full text |Cite|
|
Sign up to set email alerts
|

Removal of long-acting reversible contraceptive methods and quality of care in Dar es Salaam, Tanzania: Client and provider perspectives from a secondary analysis of cross-sectional survey data from a randomized controlled trial

Alexandra Wollum,
Corrina Moucheraud,
Amon Sabasaba
et al.

Abstract: Access to removal of long-acting reversible contraception (LARCs) (e.g., implants and intrauterine devices (IUDs)) is an essential part of contraceptive care. We conducted a secondary analysis of cross-sectional survey data from a randomized controlled trial. We analyzed 5,930 client surveys and 259 provider surveys from 73 public sector facilities in Tanzania to examine the receipt of desired LARC removal services among clients and the association between receipt of desired LARC removal and person-centered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Beyond Bias is one of very few interventions to date that directly targets health worker bias in family planning service provision [ 4 , 14 – 16 ]. In a randomized controlled trial, the intervention was found to effectively change biased attitudes and beliefs and improve quality of care for young women [ 14 , 17 ]. These results have generated broad enthusiasm for scaling-up the intervention to other settings and institutionalizing the intervention through collaborations with Ministries of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond Bias is one of very few interventions to date that directly targets health worker bias in family planning service provision [ 4 , 14 – 16 ]. In a randomized controlled trial, the intervention was found to effectively change biased attitudes and beliefs and improve quality of care for young women [ 14 , 17 ]. These results have generated broad enthusiasm for scaling-up the intervention to other settings and institutionalizing the intervention through collaborations with Ministries of Health.…”
Section: Introductionmentioning
confidence: 99%